Terms of reference for the African Opportunity Crops Working Group of the African Seed and Biotechnology Programme - Bioversity International (2025)
Across Africa, smallholder farmers, small- and medium-sized enterprises, researchers, and policymakers recognize the untapped potential of neglected and underutilized species (NUS) or opportunity crops. Yet, their ability to benefit from these crops is constrained by fragmented policies, limited access to quality seeds, and insufficient technical and market support. Addressing these challenges requires coordinated action and knowledge sharing across countries and institutions.